Gaming through the pain: psychological flow and self-efficacy amid musculoskeletal challenges in eSports - Alqabbani, Samiah; Alhussaini, Reema; Alsaedan, Shumukh; Alfaqi, Manar; Almudaifer, Reema; Zainaldeen, Najd; Alsaeed, Hanan; Algabbani, Maha; Alahmari, Wafa; Almuwais, Afrah; Alotaibi, Madawi (Frontiers in Psychology, 2025)
IntroductionThe rapid expansion of eSports has highlighted concerns regarding the physical and psychological well-being of professional gamers, which have intensified.MethodsThis study examined the prevalence of Musculoskeletal (MSK) pain and its association with flow states and self-efficacy among two hundred and thirty-two male professional gamers registered with the Saudi eSports Federation. Participants completed validated tools: the Extended Nordic Musculoskeletal Questionnaire, Flow 4D16, and General Self-Efficacy Scale (GSE-3). Descriptive and multivariate analyses were used.ResultsMSK pain was highly prevalent (72%), especially in the neck (38.4%), lower back (31.5%), and wrists/hands (24.1%). Logistic regression identified input tool and device category as significant predictors of shoulder pain (p < 0.05). Despite widespread pain, flow and self-efficacy scores remained moderate to high, with no significant associations between psychological outcomes and MSK pain (MANCOVA, Pillai's Trace = 0.044, p = 0.069).DiscussionThese findings suggest a degree of psychological resilience among eSports athletes, underscoring the complexity of physical-psychological interplay in gaming contexts. Future studies should explore mediating factors such as pain coping, motivation, and recovery behaviors.